2006
DOI: 10.1159/000094250
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Approaches for Treating Advanced Clear Cell Renal Carcinoma

Abstract: The mainstay of any curative treatment in renal cell carcinoma (RCC) is surgery. In the case of metastatic disease at presentation, a radical nephrectomy is recommended to good performance status patients prior to the start of cytokine treatment. Interferon (IFN)-a offers in a small but significant percentage of patients advantage in overall survival. Interleukin (IL)-2-based therapy gives similar survival rates. To date, hormonal therapy and chemotherapy do not have a proven impact on survival. Recent insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…Others have shown that IFN may increase IL-10 [26], which was possibly prevented by our maintenance dose. For the treatment of metastatic RCC, the tyrosine kinase inhibitors sorafenib and sunitinib are currently changing the therapeutic paradigm [7,27] and have led to a decrease in the use of IL-2 and IFN-α, the cytokines that have been the mainstay of therapy for 2 decades. Several studies are currently evaluating the combination of tyrosine kinase inhibitors with IFN-α, Gottlob et al [28] presented data of 40 patients with metastatic RCC treated with sorafenib and IFN-α.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that IFN may increase IL-10 [26], which was possibly prevented by our maintenance dose. For the treatment of metastatic RCC, the tyrosine kinase inhibitors sorafenib and sunitinib are currently changing the therapeutic paradigm [7,27] and have led to a decrease in the use of IL-2 and IFN-α, the cytokines that have been the mainstay of therapy for 2 decades. Several studies are currently evaluating the combination of tyrosine kinase inhibitors with IFN-α, Gottlob et al [28] presented data of 40 patients with metastatic RCC treated with sorafenib and IFN-α.…”
Section: Discussionmentioning
confidence: 99%
“…The overall response rate was 13.9 vs. 2.2% for controls with a 1-year survival of 53 vs. 43% and a median survival improvement of 3.8 months (p = 0.007). IL-2-based therapy gives similar survival rates [1]. In summary, these data indicate a small survival advantage for IFN-α.…”
Section: Introductionmentioning
confidence: 56%
“…In a recent review, we discussed the targeted approaches in advanced clear cell carcinoma [1]. Since that publication, the data form 3 randomized studies have been presented at several international symposia.…”
Section: Introductionmentioning
confidence: 99%
“…These new agents are small molecule inhibitors of the vascular endothelial growth factor receptor (VEGFR) and related receptors which have been proven effective in clinical trials. 2 compounds have been approved for the treatment of advanced or metastatic RCC in Europe in 2006, sunitinib and sorafenib [4]. Both compounds target VEGFR 2 and 3, and platelet-derived growth factor (PDGF) receptor β, c-KIT and FLT-3, but nevertheless differ distinctively in their profile: sunitinib also inhibits VEGFR 1, PDGFR α, RET, and CSF 1R, whereas sorafenib has been shown to block the activity of RAF kinases, which has been considered a molecular target for tumor therapies in different malignancies [5,6].…”
Section: Introductionmentioning
confidence: 99%